Mixed Convection Heat Transfer of Al2O3-H2O Nanofluid in a Trapezoidal Lid-driven Cavity at Different Angles of Inclination - Akeel Abdullah Mohammed; Maria Thaer (Zien Journals, 2022)
Mixed convection in a trapezoidal lid driven cavity containing a heat source circular cylinder using two fluids separately
Keywords: mixed convection; triangular cavity; lid-driven; adiabatic body